REINTERPRETASI KEWARISAN ISLAM BAGI PEREMPUAN - Supriyadi, Tedi (Sosio Religi: Jurnal Kajian Pendidikan Umum, 2016)
One of the issues that arose after the death deals with the distribution of property to whom and how many parts to be retrieved, this has been set forth in the law of Islam, but heir issues that until recently often contentious and prone to conflict within the family is a woman of inheritance in Islamic inheritance system is different with men so that it appears that the laws of inheritance law stigma Islam tended to be discriminatory and gender bias, this is due to the assumption that the system of inheritance in Islam is something that is taken for granted, even though the formulation of inheritance in the books of Fiqh is the interpretation of scholars in social settings where the cleric lived therefore needs to be done upon the reinterpretation of the system of inheritance for women simply because the law is a social response will continue to interact with the construction of the social life of the community